Analisis Faktor Pendukung dan Faktor Penghambat dalam Pelaksanaan Pemanfaatan Aset Tetap Badan Layanan Umum (BLU): Studi Kasus pada Politeknik Keuangan Negara STAN - Trisepti Wahyuningsih (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2021)
This study aims to analyze the factors that support and hinder the implementation of the utilization of fixed assets in BLU with a case study on PKN STAN. PKN STAN is one of the BLU of education in Indonesia. The factors used to refer to agency theory, rational choice theory, Edward III theory, and a review of previous research. This research uses an explorative qualitative analysis method. Data collection uses virtual semi-structured in-depth interview techniques. The results showed that the supporting factors for the utilization of fixed assets in BLU are Human Resources, Regulation, Supervision and Control, the Role and Commitment of Leader, and Tariff. Whereas, the inhibiting factors are Activity Management, Human Resources, Regulation, the Role and Commitment of the Leader, and Governance. This research implies that BLU has a significant role in optimizing the utilization of its fixed assets through Human Resources management and activity management. Besides, regulators also play a role in strengthening the flexibility of BLU within the scope of the utilization of fixed assets through clear regulations.